A Comparison of Later Stage Dental Maturation in a Small Group of Children from Chernobyl and British Children - H. M. Liversidge; C. E. A. Rogers (Dental Anthropology Association, 2001)
The aim of this study was to investigate the dental radiographic development of a small group of children born in Chernobyl, Ukraine, around the time of the nuclear disaster with an age matched group of British children. The design was a cross sectional non random retrospective study consisting of five boys and five girls from Chernobyl (age range 10.03 to 12.37) and 20 age and sex matched British children of white Caucasian origin. Developing permanent mandibular teeth were assessed from rotational tomograms using criteria described by Demirjian, Goldstein and Tanner (1973). Third molar formation was also assessed. Dental age was calculated and compared to real age using a t-test. The difference in dental age (DA) and real age (RA) was not significant when the two groups were compared. Dental age in both groups of children was advanced compared to the standards. These results suggest that the Chernobyl disaster has not affected root formation of late forming permanent teeth of these children.